Neuroimaging of Consciousness and Sleep Spindles - Urakami, Yuko (Recent Patents on Medical Imaging (Discontinued), 2013)
It has become feasible to study several aspects of consciousness because of recent progress in the neuroscience of perception, memory, and action, and advances in techniques of neuroimaging of human brain function. Consciousness has 2 main components: level of arousal (wakefulness) and content of consciousness (self awareness). Level of arousal has been investigated with electric correlates and structures in the brainstem and diencephalons that regulate the sleepwake cycle. From a behavioral and neurobiological perspective, sleep and consciousness are intimately connected. Recent functional brain imaging has been used in humans to investigate the neural mechanisms underlying the generation of sleep stages. Sleep consolidates new memories, and spindle activity is associated with improvements in procedural and declarative memory. The sleeping brain processes external information and detects the pertinence of its context. A default mode of brain function may explain consistent decreases in brain-activity during cognitive processing as compared to a passive resting state. The recent advances in neuroimaging, including functional magnetic resonance imaging (fMRI), magnetic resonance spectroscopy (MRS), and diffusion tensor imaging (DTI) are reviewed with a focus on the possibility of prognostic tools to evaluate consciousness disturbance such as coma. Also recent advances in functional brain imaging and combined methods of electroencephalogram and magnetoencephalogram and/or fMRI, are reviewed with a focus on the progress on the evaluation of normal sleep physiology. Patents as neuroimaging tools in this field are introduced.
Keywords: default mode network